The Flow-Induced Degradation and Vascular Cellular Response Study of Magnesium-Based Materials - Shang, Tengda; Wang, Kebing; Tang, Shusheng; Shen, Yang; Zhou, Lei; Zhang, Lu; Zhao, Yuancong; Li, Xin; Cai, Lin; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium (Mg)-based materials are considered as potential materials for biodegradable vascular stents, and some Mg-based stents have obtained regulatory approval. However, the development and application of Mg-based stents are still restricted by the rapid degradation rate of Mg and its alloys. In order to screen out the desirable Mg-based materials for stents, the degradation behavior still needs further systematic study, especially the degradation behavior under the action of near-physiological fluid. Currently, the commonly used Mg-based vascular stent materials include pure Mg, AZ31, and WE43. In this study, we systematically evaluated their corrosion behaviors in a dynamic environment and studied the effect of their degradation products on the behavior of vascular cells. The results revealed that the corrosion rate of different Mg-based materials was related to the composition of the elements. The dynamic environment accelerated the corrosion of Mg-based materials. All the same, AZ31 still shows good corrosion resistance. The effect of corrosive products on vascular cells was beneficial to re-endothelialization and inhibition of smooth muscle cell proliferation at the implantation site of vascular stent materials.